The Role of Modern Technology in Enhancing Sustainable Urban Renewal (Journal of Planner and Development, 2024)
Abstract: Amid the complex challenges facing contemporary cities, including environmental pressures, rapid population growth, and the urgent need to improve the quality of life for residents, the question of how modern technology can support efforts towards sustainable urban renewal arises. These motivations form the foundation of this research, which aims to explore the potentials offered by technology in achieving more sustainable cities capable of adapting to future challenges. The purpose of this research is to assess the role those modern technologies, including but not limited to artificial intelligence, information and communication technology, big data, and smart transportation systems, can play in enhancing sustainable urban renewal efforts. The research seeks to explore how these technologies can contribute to improving environmental sustainability, economic efficiency, and social justice within the urban fabric, as well as examining the challenges and opportunities associated with their application in various urban contexts. The findings reveal a pivotal importance of modern technology in supporting and enhancing sustainable urban renewal, as it provides effective tools for improving resource use efficiency, enhancing transportation systems, improving the quality of the urban environment, and fostering inclusivity and community participation. Additionally, the study indicates that the integration of modern technologies can contribute to finding innovative solutions for adapting to environmental and demographic changes, leading to cities that are more flexible and capable of adapting to the future. However, the study also emphasizes the importance of considering the challenges related to technological integration and the need for a comprehensive framework that ensures the optimal use of these technologies in the context of sustainable urban renewal.